Analysis of social media marketing activities of Hungarian accommodation providers and catering SME’s from the aspect of lean principles - Nyikos Bendegúz Richárd; Keresztes Gábor; Pankotay Fruzsina Magda (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. Lean management can be viewed as an attitude that organizes and directs business processes while keeping a few main guiding principles in focus such as maximizing the customer value while minimizing losses, resulting in the creation of increased customer value by using fewer resources. The lean thinking can successfully applied in the field of social media marketing when it comes to understanding the logical process of the individual operations and to increase the overall efficiency of the campaigns while improving the key performance indicators. The basic principles of lean can serve as the basis in any system and in any business, and for this reason, basic principles are also taken into consideration at strategic levels. The various platforms have become smart, the advertising alternatives can be highly customized based on the individual needs of businesses, which can also result in higher overall efficiency. With the help of the available social media platforms, businesses are not only able to reach their desired audience but can also measure the success of their individual campaigns. The main goal of the research is to find an answer to what parallels and connections can be discovered between online marketing and lean theories. The research aims to answer the questions of how the process of creating and maintaining social media marketing strategies can be characterized from the aspect of lean thinking while focusing on discovering whether the origin of the individual campaigns – either in-house or outsources – have any effect on the extent of how well the lean principles are applied. During the course of the research, accommodation providers and catering SMEs located in various Hungarian cities were visited in order to use a questionnaire to assess the social media marketing processes of the given units.The research proved that 70% of the social media activity in the examined region was outsourced and the vast majority of businesses (57%) do not track the effectiveness of their marketing activities regularly. The potential presence of lean in marketing processes had been monitored.

A lean menedzsment olyan attitűdként fogható fel, amely megszervezi és irányítja az üzleti folyamatokat, miközben néhány fő vezérelvet fókuszban tart, mint például a vásárlói érték maximalizálása a veszteségek minimalizálása mellett, ami kevesebb erőforrás felhasználásával megnövelt ügyfélértéket eredményez. A lean gondolkodás sikeresen alkalmazható a közösségi média marketing területén az egyes műveletek logikai folyamatának megértésében, a kampányok általános hatékonyságának növelésében, a fő teljesítménymutatók javítása mellett. A lean alapelvei minden rendszer és vállalkozás működési hatékonyságnövelésében fundamentumként szolgálhatnak, ezért ezeket az alapelveket stratégiai szinten is figyelembe veszik. A különböző platformok okossá váltak, a reklámalternatívák a vállalkozások egyedi igényei alapján nagymértékben testreszabhatók, ami egyben magasabb összhatékonyságot is eredményezhet. A rendelkezésre álló közösségi média platformok segítségével a vállalkozások nemcsak a kívánt közönséget érhetik el, hanem egyéni kampányaik sikerét is mérhetik. A kutatás fő célja, hogy választ találjon arra, milyen párhuzamosságok és összefüggések fedezhetők fel az online marketing és a lean elméletek között. A kutatás arra a kérdésre kíván választ adni, hogy a közösségi média marketingstratégiák létrehozásának és fenntartásának folyamata miként jellemezhető a lean gondolkodás szempontjából, annak felderítésére összpontosítva, hogy az egyes kampányok indítása – akár házon belüli, akár kiszervezett – van-e hatással arra, hogy milyen mértékben alkalmazzák a lean elveket. A kutatás során különböző magyarországi városokban található szálláshely-szolgáltatókat és vendéglátóipari KKV-kat kerestünk fel, hogy kérdőív segítségével felmérjük az adott egységek közösségi média marketing folyamatait. Kérdések sorozata segített többet megtudni arról, hogy a vállalkozások hogyan tervezik és használják a közösségi média marketing gyakorlatait.

Резюме. Концепція Lean-менеджменту може розглядатися як підхід, що організовує та керує бізнес-процесами, зосереджуючись при цьому на кількох основних принципах, таких як максимізація цінностей для клієнта при мінімізації витрат, що призводить до створення більших цінностей для споживача за рахунок використання меншої кількості ресурсів. Leanмислення успішно може застосовуватися в галузі маркетингу соціальних мереж, коли мова йде про розуміння логічного процесу окремих операцій та підвищення загальної ефективності кампаній при одночасному покращенні ключових показників результативності. Основні принципи Lean («ощадливі» принципи) можуть служити основою у будь-якій системі та бізнесі, зокрема враховуються і на стратегічних рівнях. Різноманітні платформи стали смарт (розумними), рекламні альтернативи можна налаштовувати відповідно до індивідуальних потреб бізнесу, що також призводить до більшої загальної ефективності. За допомогою доступних платформ соціальних мереж, бізнес може не тільки залучати власну цільову аудиторію, але й вимірювати успіх окремих кампаній. Основна мета дослідження полягає у пошуку відповіді на питання, які паралелі та зв'язки можна виявити між онлайн-маркетингом та Lean-теоріями. Дослідження розкриває процес створення та підтримку стратегій маркетингу соціальних мереж з точки зору Lean-мислення, зосереджуючись на виявленні впливу окремих кампаній – внутрішніх або зовнішніх - на ступінь використання принципів Lean. У процесі дослідження проведено анкетування постачальників послуг розміщення та малих підприємств кейтерингу, які функіонують в різних містах Угорщини, з метою оцінки ефективності їх процесів маркетингу в соціальних мережах. Дослідження показало, що 70% активності соціальних медіа в досліджуваному регіоні було передано аутсорсингу, а переважна більшість компаній (57%) не контролюють ефективність своєї маркетингової діяльності регулярно. Проведено моніторинг потенційної присутності Lean у маркетингових процесах.
Аналіз маркетингової діяльності угорських постачальників сфери розміщення та малих підприємств громадського харчування у соціальних мережах на основі Lean-принципів
A magyar szállásadók és vendéglátó kkv-k közösségi média marketing tevékenységének elemzése a LEAN elvek alapján
https://aab-economics.kmf.uz.ua/aabe/issue/view/3
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00012366
Keywords: lean management; social media marketing; SME sector